Prognostic Value of 3 Nutritional Screening Tools to Predict 30-Day Outcome in Patients Undergoing Carotid Artery Stenting. (March 2022) - Çakmak, Ender Ö; Öcal, Lütfi; Erdoğan, Emrah; Cerşit, Sinan; Efe, Süleyman Çağan; Karagöz, Ali; Yılmaz, Fatih; Fidan, Serdar; Alizade, Elnur; Zehir, Regayip; Kırma, Cevat
The effect of malnutrition on outcomes after carotid artery stenting (CAS) is not well known. This study reports the relationship between malnutrition and post-procedure 30-day major adverse events (MAEs). A total of 978 patients hospitalized for CAS were enrolled in the study. Controlling nutritional status (CONUT) score, the nutritional risk index (NRI), and the prognostic nutritional index (PNI) were calculated. MAEs (myocardial infarction, stroke/transient ischemic attack and mortality) were compared. According to the CONUT score, NRI, and PNI, 9.4%, 41%, and 11.4% patients were moderately or severely malnourished, respectively; 74.8% were at least mildly malnourished by at least 1 score. Forty-seven patients (4.8%) had a post-procedure 30-day MAE. Continuous classifications of the indexes were independently associated with higher MAE. CONUT showed the highest predictive ability, whereas NRI had the lowest (C-index: CONUT, 0.701; NRI, 0.681; PNI, 0.688). According to categorical classification of indexes, only CONUT and PNI showed predictive ability for MAE. Malnutrition assessment could identify patients with CAS at elevated risk for MAE. CONUT, NRI, and PNI continuous scores were independent prognostic factors for the post-procedure 30-day MAE. According to our study, CONUT showed the highest predictive ability.